'Montezuma's revenge': neurological disorders in the returning traveller. Issue 5 (24th July 2018) - Bharucha, Tehmina; Manji, Hadi
Abstract : 'The world is a book and those who do not travel read only one page'. Augustine of Hippo – Latin philosopher and theologian. Neurological presentations are seen in about 1.5%–2.0% of returning travellers seeking medical attention, and may pose a particular challenge to diagnose and treat. These may be severe and life threatening, such as meningoencephalitic illnesses or inflammatory radiculoneuropathy (Guillain-Barré-like) syndromes requiring intensive care support. It is essential not to miss the potentially treatable and common diseases such as malaria, which can be lethal if undiagnosed. Herpes simplex virus remains the most common cause of encephalitis in returning travellers to the UK. Furthermore, common bacterial conditions such as pneumococcal meningitis may be associated with different resistance patterns globally, and this must be taken into account in treatment decisio.ns. This review provides a clinical approach, illustrated with a range of cases, and suggestions where to get further management advice.